Association of miR-122 and miR-21 with the severity of HDV infection - Joldasova, Elizaveta; Ibadullaeva, Nargiz; Khikmatullaeva, Aziza; Abdukadirova, Muazzam; Khodjaeva, Malika; Bobkova, Marina; Musabaev, Erkin (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Hepatitis D is the most severe manifestation of chronic viral hepatitis, characterized by significant clinical ramifications. These repercussions encompass an elevated susceptibility to hepatic decompensation and the development of hepatocellular carcinoma (HCC), ultimately culminating in fatal outcomes. The role of miRs in the pathogenesis of this disease remains largely unexplored. Methods: The study enrolled 102 treatment naïve chronic hepatitis D patients. 31 patients had chronic hepatitis D and 71 patients liver cirrhosis of HDV aetiology. The EIA confirmed HDV infection with the following quantitative PCR. Results: Compared to LC patients, those with CHD showed significantly higher levels of miR-122 and lower levels of miR-21. miR-122 expression inversely correlated with the severity of liver cirrhosis, showing lower numbers in the group with LC Class A compared to the LC Class B. Meanwhile, the group of patients without liver cirrhosis had the highest values.  miR-21 was also higher in the LC Class A group compared to LC class B and patients without liver cirrhosis. Conclusions: miR-122 and miR-21 could serve as an effective predictor for further decompensation of liver cirrhosis and exacerbation of the HDV infection process. This assumption requires further study in a larger sample.